Emergence of biopharmaceutical innovators in China, India, Brazil, and South Africa as global competitors and collaborators - Rezaie Rahim; McGahan Anita M; Frew Sarah E; Daar Abdallah S; Singer Peter A (BMC, 2012)
Abstract Biopharmaceutical innovation has had a profound health and economic impact globally. Developed countries have traditionally been the source of most innovations as well as the destination for the resulting economic and health benefits. As a result, most prior research on this sector has focused on developed countries. This paper seeks to fill the gap in research on emerging markets by analyzing factors that influence innovative activity in the indigenous biopharmaceutical sectors of China, India, Brazil, and South Africa. Using qualitative research methodologies, this paper a) shows how biopharmaceutical innovation is taking place within the entrepreneurial sectors of these emerging markets, b) identifies common challenges that indigenous entrepreneurs face, c) highlights the key role played by the state, and d) reveals that the transition to innovation by companies in the emerging markets is characterized by increased global integration. It suggests that biopharmaceutical innovators in emerging markets are capitalizing on opportunities to participate in the drug development value chain and thus developing capabilities and relationships for competing globally both with and against established companies headquartered in developed countries.